Energy and emissions effects of airtightness for six non-residential buildings in Canada with comparison to contemporary limits and assumptions. (15th October 2022) - Banister, Carsen; Bartko, Michal; Berquist, Justin; Macdonald, Iain; Vuotari, Mark; Wills, Adam
Abstract: Building air leakage is often a significant contributor to the energy consumption of a building and is difficult to characterize. Unlike the thermal performance of building envelope components, the high variability of airtightness of building assemblies and their interfaces makes air leakage of buildings difficult to predict. This publication describes the process and results for identifying leakage rates and locations within six non-residential buildings using airtightness testing, specifically six commercial buildings. Infrared (IR) scanning was used to visualize locations of air leakage in the building envelope. The energy and emissions effects from the measured performance were quantified and compared to the assumption in the relevant Canadian building code. The air leakage rates for all buildings tested in this work were less than the ASHRAE 90.1 standard limit of 2.0 L·s −1 m −2 @ 75 Pa, while three were less than the Air Barrier Association of America (ABAA)/United States Army Corps of Engineers (USACE) standard limit of 1.25 L·s −1 m −2 @ 75 Pa, and two were less than the National Energy Code of Canada for Buildings (NECB) assumption of 1.5 L·s −1 m −2 @ 75 Pa (a different area normalization is used for the NECB). The effects of airtightness on energy use intensity and annual operational emissions were quantified and found to be substantial and varied. The incremental energy use intensity ranged from a reduction of 47 kWh/m 2 ᐧyear to an addition of 64 kWh/m 2 ᐧyear. The most common location of leakage is between connections of building assemblies, especially the roof wall connection, and building components, particularly doorways, as well as at various envelope penetrations, such as for pipes and ventilation inlets/exhausts. The process of testing was documented and showed that the use of currently-available commercial equipment enables tests for typical small to medium-sized commercial/non-residential buildings to be completed efficiently. The results showed there is notable variation in airtightness levels between buildings and there are opportunities for improvement. Highlights: Blower door and infrared imaging airtightness testing of 6 non-residential buildings. Competent practitioners were readily available to conduct tests. Airtightness testing process, cost, and time are presented. Energy and emissions effects are quantified in comparison to benchmarks.